Faktor Penghambat dalam Implementasi Asuransi Usaha Ternak Sapi di Kabupaten Gowa - Nita Adillah Pratiwi; Sitti Nurani Sirajudin; Aslina Asnawi (Journal Agro-Livestock, 2023)
Livestock Insurance (LI) is a contract in which the insurance company provides protection and the farmer receives protection. In this agreement, the farmer pays an insurance premium to the insurance company in exchange for reimbursement if their livestock die due to disease, accident, birth, or loss in line with the terms and conditions of the insurance policy.. Farmers who use LI face numerous challenges, ranging from the registration process to the claims process when cattle die. Of course, the number of breeders joining LI has fluctuated due to a variety of factors, one of which is the difficulties that breeders face. The purpose of this study is to identify the factors impeding livestock in the implementation of Cattle Business Insurance in Gowa Regency. The data analysis done in this study is factor analysis to discover the factors that have the most influence. The research findings indicate that there are several impediments to the implementation of AUTS in Gowa Regency, with four factors influencing the most, namely a lack of socialization regarding AUTS, claims procedures that are poorly understood, the length of disbursement during claims, and the short time given at the time of claim.